2005
DOI: 10.4049/jimmunol.174.6.3493
|View full text |Cite
|
Sign up to set email alerts
|

Genes “Waiting” for Recruitment by the Adaptive Immune System: The Insights from Amphioxus

Abstract: In seeking evidence of the existence of adaptive immune system (AIS) in ancient chordate, cDNA clones of six libraries from a protochordate, the Chinese amphioxus, were sequenced. Although the key molecules such as TCR, MHC, Ig, and RAG in AIS have not been identified from our database, we demonstrated in this study the extensive molecular evidence for the presence of genes homologous to many genes that are involved in AIS directly or indirectly, including some of which may represent the putative precursors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 59 publications
5
34
0
Order By: Relevance
“…Immunocytes (coelomocytes) of amphioxus were first discovered in the gut region 25 yr ago (Rhodes et al 1982). Our studies have further confirmed that gill and gut represent the major immune region in amphioxus Yu et al 2005Yu et al , 2007bHuang et al 2007a,b;Yuan et al 2007). Unfortunately, since the year 1982, only a few studies address the amphioxus immunity.…”
supporting
confidence: 75%
“…Immunocytes (coelomocytes) of amphioxus were first discovered in the gut region 25 yr ago (Rhodes et al 1982). Our studies have further confirmed that gill and gut represent the major immune region in amphioxus Yu et al 2005Yu et al , 2007bHuang et al 2007a,b;Yuan et al 2007). Unfortunately, since the year 1982, only a few studies address the amphioxus immunity.…”
supporting
confidence: 75%
“…The earliest forms of secondary lymphoid tissue were diffuse aggregations and infiltrations in the intestinal wall [60].The implication is that many of the functions which we associate with organised lymphoid tissues in mammals (collections of B-cell follicles and associated T-cell zones) originally took place in more diffuse aggregations of leucocytes in mucosal tissues. Consistent with this idea, immunologically-related genes appear to be expressed preferentially in the intestine in the protochordate amphioxus and in the jawless lampreys [50,59]. Since mucosal tissues are permanently exposed to both harmless as well as harmful antigens, mechanisms must exist which activate appropriate, but different responses to different types of antigens.…”
Section: Structure Of the Mucosal Immune Systemmentioning
confidence: 87%
“…These include the FREP genes in snails that are thought to diversify through alternative splicing and gene conversion (30,51; reviewed in Ref. 24), the VCBP gene family in Amphioxus (6 -8, 22, 23, 51), and the antimicrobial penaeidins in shrimp (10,15,31).…”
Section: Paradigm Shiftmentioning
confidence: 99%